Preparing for new competitive challenges: Special issue on the 24th annual IPSERA conference. Issue 3 (September 2016) - Kamann, Dirk-Jan F.; Dullaert, Wout; de Leeuw, Sander
Abstract: The 24th IPSERA conference in Amsterdam addressed the various new competitive challenges organisations face now that business environments are rapidly changing. While we can observe an increased role of - but also an increased concentration in - logistic services and IT services acting as a bonding agent of the various business processes, we also see an increased specialisation among suppliers, resulting in roles like capacity supplier, co-maker and broker. In terms of Systems Thinking: the sub-system of 'Suppliers' is breaking up into three sub-systems with distinctive different characteristics, and the traditional sub-system 'Purchasing' has transformed into an aspect-system connecting or involving all other sub-systems, while similarly, 'Logistics' and 'IT' have developed into intertwined aspect-systems, being part of each and every sub-system. These transformations have increased managerial complexity, greatly influencing the purchasing and supply chain functions within firms. The seven papers selected from the conference examine seven aspects of those changes in detail and elaborate on the role of the PSM field in this process: PSM responds to challenges by providing answers on how to move forward in practice.